A history of English literature - Alexander, Michael (Palgrave Macmillan, 2007)
The second edition of this best-selling book has been completely updated and revised throughout to take into account new authors and new scholarly developments in literature and in society. Offering a comprehensive account of one of the world's richest literatures, A History of English Literature traces its developments from the Old English period until the present day.